Pulmonary Artery Dissection Following Severe Pulmonary Artery Hypertension - Diasmada A., et al (ACI (Acta Cardiologia Indonesiana), 2017)
Pulmonary Artery Dissection Following Severe Pulmonary Artery Hypertension